2011
DOI: 10.1177/0733464811402198
|View full text |Cite
|
Sign up to set email alerts
|

Workers’ Experiences of Crises in the Delivery of Home Support Services to Older Clients

Abstract: In the provision of care to older clients, home support workers regularly confront, avert, and manage crises. Semistructured interviews were conducted to explore the nature, type, and management of crises from the perspective of home support workers (N = 118) of older persons in British Columbia, Canada. The delivery of home health care occurs within a context of unpredictability related to scheduling, time constraints, variability of client need, and changing work environments. These events are experienced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(59 citation statements)
references
References 34 publications
4
55
0
Order By: Relevance
“…Household cleaning is now rarely funded by Social Services, and respondents argued that when clients did not have alternative resources to provide this cleaning, homes could become dirty. Instead of proposed harmful cuts to domiciliary care there should be sufficient funding and appropriate policies to offer domiciliaries a safe workplace (Rubery and Urwin, 2011;Sims-Gould et al, 2011). Mirroring Dyck et al's (2005) calls for changes in Canada, domiciliary care policies in England and elsewhere must also be expanded to ensure that care is re-introduced for the client's home where necessary, rather than relying on domiciliaries to perform unrecognised work in managing dirty workplaces, for the wellbeing of both clients and staff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Household cleaning is now rarely funded by Social Services, and respondents argued that when clients did not have alternative resources to provide this cleaning, homes could become dirty. Instead of proposed harmful cuts to domiciliary care there should be sufficient funding and appropriate policies to offer domiciliaries a safe workplace (Rubery and Urwin, 2011;Sims-Gould et al, 2011). Mirroring Dyck et al's (2005) calls for changes in Canada, domiciliary care policies in England and elsewhere must also be expanded to ensure that care is re-introduced for the client's home where necessary, rather than relying on domiciliaries to perform unrecognised work in managing dirty workplaces, for the wellbeing of both clients and staff.…”
Section: Discussionmentioning
confidence: 99%
“…All of these factors applied in this study. In contrast Sims-Gould et al (2011) suggest that hazardous homes are only a result of a 'crisis', and whilst this may be the case in some households, for others it may be a long-term problem as Typically, contemporary workplaces are portrayed as welcoming, sanitised offices as a respite from home (Reeves, 2001), yet for domiciliaries whose workplace is someone else's home they may not enjoy this 'respite'. To illustrate, one house visited with Louise and Joanna (domiciliaries) was neglected and rundown.…”
Section: Dirty Workplaces?mentioning
confidence: 99%
“…There is a substantial amount of research on home as a place of care (Twigg, 1999;Vilkko, 2000;Wiles, 2003Wiles, , 2005Dyck et al, 2005;Martin-Matthews, 2007;Phillips and Martin-Matthews, 2008;Cloutier et al, 2015). On the one hand, research has focused on the experiences of older people receiving care in their own homes (for example Twigg, 1999;Dyck et al, 2005), and on the other hand, on care workers' experiences of caring for older people in the older people's homes (Mahmood and Martin-Matthews, 2008;Sims-Gould et al, 2013). In adult foster care, a home is a more complex site of study as it is usually the foster carer's home before it becomes a place of care for 'strangers' and eventually, at least ideally, a home for these strangers, that is, older people in need of care.…”
Section: Boundaries Of the Place Called Homementioning
confidence: 99%
“…The social environment issues range from additional tasks to distractions from pets, children and televisions (strong evidence: Cheung et al, 2006;Hale & Piggot, 2005; moderate evidence: Leiss, 2012;Sims-Gould et al, 2013;limited evidence: Denton et al, 2002) through to issues of cleanliness and insect and rodent infestations (moderate evidence: Sims-Gould et al, 2013;Quinn et al, 2009;limited evidence: Denton et al, 2002). The close interaction can lead to additional requests from patients which were not on the treatment plan and/or outside the caregiver job description (moderate evidence : Beer et al, 2014;Skoglind-Ohman & Kjellberg, 2011;Swedberg et al, 2013;limited evidence: Denton et al, 2002).…”
Section: Environments (Health Policy Community Physical and Social)mentioning
confidence: 99%
“…Evidence was found that identified physical risks associated with inadequate and missing equipment, e.g. lifting or bathing equipment which was the incorrect size and/or weight capacity for the patient (strong evidence: Hale & Piggot, 2005;moderate evidence: Craven et al, 2012;Faucett et al, 2013;Leiss, 2012;Pohjonen et al, 1998;Simon et al, 2008;Sims-Gould et al, 2013) and a lack of support for maintenance and training in medical devices (moderate evidence: Munck et al, 2011).…”
Section: Artefacts (Equipment and Technology)mentioning
confidence: 99%